Immune response plays a role in Mycoplasma pneumoniae pneumonia - Zhu, Yifan; Luo, Yingying; Li, Ling; Jiang, Xinyi; Du, Yi; Wang, Jing; Li, Huilin; Gu, Haiyan; Li, Daiying; Tang, Heng; Qin, Houbing; Xu, Changdi; et al. (Frontiers in Immunology, 2023)
Mycoplasma pneumoniae (MP) is a major pathogen of community-acquired pneumonia in children. However, the specific pathogenesis of the progression of Mycoplasma pneumoniae pneumonia (MPP) is unclear. This self-controlled study analyzed the microbiome and transcriptome of bronchoalveolar lavage fluid (BALF) from the severe side (SD) and opposite side (OD) of 41 children with MPP from January to December 2021 and revealed the differences of the peripheral blood neutrophil function among children with mild MPP, severe MPP, and healthy children through transcriptome sequencing. The MP load or the pulmonary microbiota had no significant difference between the SD group and OD group, and the deterioration of MPP was related to the immune response, especially the intrinsic immune response, which may inform treatment strategies for MPP.